Cards that farmers CAN read: on the way to improving the effectiveness of the Government of India’s Soil Health Card Scheme - CGIAR Research Program on Policies, Institutions, and Markets (2018)
India's Soil Health Card Scheme aims to provide every farmer with a card containing recommendations to improve management practices based on local soil measures. PIM found that farmers were not able to understand these cards, and designed a clearer and more user-friendly version. After testing and distribution of the redesigned cards in the state of Bihar, the Ministry of Agriculture plans to expand their use to the national level.